The effect of bank capital to its performance: Evidences from Vietnamese commercial banking system - NGUYEN, THI THU TRANG (2018)
This study objects to analyse the effect of bank capital to banks’ probability of survival, market share and profitability, which are three main indicators of banks’ performance in Vietnamese commercial banking system during the period of 2011 – 2017. Following the methodology of Berger and Bouwman (2013), the regression model would be applied to examine the effects of bank capital ratio and other determinants banks’ profitability, market share and profitability, respectively. Accordingly, with annual panel data, the findings show the positive relationship of bank capital to its probability of survival and market share, especially during the crisis and post-crisis time, whereas this capital ratio affect detrimentally to banks’ probability in Vietnamese commercial banking system from 2011 to 2017. This results clarify the reason of several policies regulated by the State bank of Vietnam, which is not only fill the literature gap of Vietnamese banking system but also give confirmation about the importance of bank capital to banks’ performance. In addition, further regression related to bank size comparison and three channels through which capital may affect bank’s performance would be included for comparison purpose.